RELIGIOUS MODERATION TO PREVENT RADICALISM IN ACEH ISLAMIC COLLEGE - Mawardi Mawardi (IAIN Kediri, 2022)
Aceh, which has had the privilege of implementing sharia law in its territory, has faced a major challenge for accusations of